A Tale of Modern Slavery - Films Media Group (2005)
Use this ABC News program to increase viewer awareness of a heartbreaking but undeniable truth-that slavery is alive and well in the 21st century. The video shows how caste systems and other archaic traditions have perpetuated slavery in some poor countries, and points to the complacency of wealthier nations regarding this ongoing tragedy. Highlighting the work of Nigerian anti-slavery activists, including the imprisoned Ilguilas Weila of the human rights group Timidria, the video also features commentary from Amnesty International USA Executive Director William Schultz, who emphasizes the need for more action from the Western world. (22 minutes).
fma35365
Mode of access: World Wide Web.
System requirements: Windows Media, etc.